White-light-induced disruption of nanoscale conducting filament in hafnia - Zhang, H. Z. (2015)
Nanoscale conducting filament, which forms the basis of the HfO2 resistive memory, is shown to exhibit a “negative photoconductivity” behavior, in that, electrical conduction through it can be disrupted upon white-light illumination. This behavior should be contrasted against the positive photoconductivity behavior commonly exhibited by oxides or perovskites having narrower bandgaps. The negative photoconductivity effect may be explained in terms of a photon-induced excitation of surrounding oxygen ions, which leads to migration and subsequent recombination with vacancies in the conducting filament. The finding suggests possible electrical-cum-optical applications for HfO2-based devices, whose functionality is limited to-date by electrical stimulation.